2019
DOI: 10.1111/dmcn.14346
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric‐onset neuronal ceroid lipofuscinosis: first symptoms and presentation at diagnosis

Abstract: Neuronal ceroid lipofuscinoses (NCLs) are rare, progressive disorders. Through this series of 20 patients with NCL, we illustrate differences between subtypes in their presenting symptoms and clinical, imaging, and electrophysiological results to raise awareness of symptom diversity. Data were available on presenting symptoms, genetics, magnetic resonance imaging (MRI), electroencephalography (including with low‐frequency intermittent photic stimulation), visual responses, and electron microscopy. Causal mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
3
37
1
Order By: Relevance
“…Although these features are suggestive of CLN2 disease, they are not specific and may be associated with other NCL variants. A study by Dozi eres-Puyravel et al on 20 patients with various NCLs identified cerebellar and cerebral atrophy at first MRI in patients with CLN1, CLN2 and CLN6 disease [6]. This study also found cerebellar atrophy at first MRI in patients with CLN7 and CLN11 disease [6].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although these features are suggestive of CLN2 disease, they are not specific and may be associated with other NCL variants. A study by Dozi eres-Puyravel et al on 20 patients with various NCLs identified cerebellar and cerebral atrophy at first MRI in patients with CLN1, CLN2 and CLN6 disease [6]. This study also found cerebellar atrophy at first MRI in patients with CLN7 and CLN11 disease [6].…”
Section: Discussionsupporting
confidence: 68%
“…A study by Dozi eres-Puyravel et al on 20 patients with various NCLs identified cerebellar and cerebral atrophy at first MRI in patients with CLN1, CLN2 and CLN6 disease [6]. This study also found cerebellar atrophy at first MRI in patients with CLN7 and CLN11 disease [6]. Nevertheless, when considered alongside clinical findings, the MRI features we have identified may provide an important clue in the early diagnosis of CLN2 disease.…”
Section: Discussionsupporting
confidence: 66%
“…Photo‐paroxysmal response (PPR) on electroencephalography induced by low‐frequency photic stimulation was previously considered as highly suggestive of NCL disorders . Dozières‐Puyravel et al found a lower rate of PPR than previous studies (33% vs 69–78%) . Such variability might be due to lack of a standardized procedure of photic stimulation, and it might be influenced by antiepileptic drugs.…”
mentioning
confidence: 97%
“…3 Delayed language acquisition frequently preceded the onset of more obvious symptoms, but in most cases language delay is under-detected both by parents and general paediatricians. 2 Recently language delay has been considered a forerunner of the disease as it was retrospectively identified in 83% of patients. 3 Based on these data, the occurrence of a first seizure (any type) in a patient with a language delay may be considered a clinical red flag for the diagnosis of CLN2 disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation